2010
DOI: 10.1093/her/cyq023
|View full text |Cite
|
Sign up to set email alerts
|

Associations between schools' tobacco restrictions and adolescents' use of tobacco

Abstract: Schools are an important arena for smoking prevention. In many countries, smoking rates have been reduced among adolescents, but the use of smokeless tobacco is on the rise in some of these countries. We aimed to study the associations between schools' restrictions on smoking and snus and on the use of these tobacco products among students in upper secondary school. We employed data from a national representative study of 1444 Norwegian students, aged 16-20 years. Respondents were asked about their schools' re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…Five of these studies16 24 30 35 37 suggested a 20% to 60% decreased probability of tobacco use among students in schools with strict bans, supported by three studies that presented an increased risk with more liberal attitudes, especially concerning smoking by teachers 11 19 40. However, other studies failed to detect clear relationships between smoking bans per se and students’ behaviour,12 18 32 38 while one study suggested an association in the opposite direction (higher likelihood of smoking progression) if the students perceived the presence of strict bans 36…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Five of these studies16 24 30 35 37 suggested a 20% to 60% decreased probability of tobacco use among students in schools with strict bans, supported by three studies that presented an increased risk with more liberal attitudes, especially concerning smoking by teachers 11 19 40. However, other studies failed to detect clear relationships between smoking bans per se and students’ behaviour,12 18 32 38 while one study suggested an association in the opposite direction (higher likelihood of smoking progression) if the students perceived the presence of strict bans 36…”
Section: Resultsmentioning
confidence: 93%
“…Concerning the modality of assessment of STPs, studies could be divided into 2 groups: 9 studies where the assessment was based exclusively on students’ subjective perception of rules and of their enforcement in school,20 21 28 31–33 36 37 40 and the remaining 22 where the assessment was performed exclusively or also through interviews or surveys of the school administrators.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations